Paradigmatic tools for communication scholar–activists: toward a pragmatic and relational epistemology. Issue 1 (2nd January 2018) - Huffman, Timothy P.
ABSTRACT: Scholars of communication who are committed to activism and social justice often do not fit fully into the paradigms of postpositive, interpretive, or critical traditions. Alternately, pragmatism and relational epistemology serve as excellent paradigmatic frameworks. Pragmatism, a tradition of philosophy that focuses on the connection between ideas and action, and relational epistemology, an approach to knowing that highlights the relationships between knowers, both offer valuable tools for scholar– activists. By engaging in communication scholarship oriented toward action and situated in relationships, scholar– activists can strive to draw on broad stakeholder experiences to contribute to interdependent human flourishing.